Widespread Striatal Delivery of GDNF from Encapsulated Cells Prevents the Anatomical and Functional Consequences of Excitotoxicity. (11th March 2019) - Emerich, Dwaine F.; Kordower, Jeffrey H.; Chu, Yaping; Thanos, Chris; Bintz, Briannan; Paolone, Giovanna; Wahlberg, Lars U.
Abstract : Methods . Human ARPE-19 cells engineered to secrete high levels of the glial cell line-derived neurotrophic factor (GDNF) were encapsulated into hollow fiber membranes. The devices were implanted into the rat striatum 1 week prior to striatal quinolinic acid injections. Animals were evaluated using a battery of validated motor tests, and histology was performed to determine the extent of GDNF diffusion and associated prevention of neuronal cell loss and behavioral deficits. Results . Encapsulated cell-based delivery of GDNF produced widespread distribution of GDNF throughout the entire implanted striatum. Stereological estimates of striatal neuron number and volume of lesion size revealed that GDNF delivery resulted in near complete neuroprotection. Conclusions . Delivery of neurotrophic molecules such as GDNF using encapsulated cells has reached a technological point where clinical evaluation is justified. Because GDNF has been effective in animal models of Parkinson's disease, stroke, epilepsy, and Huntington's disease, among other debilitating neurodegenerative diseases, encapsulated cell-based delivery of GDNF might represent one innovative means of slowing the neural degeneration seen in a myriad of currently untreatable neurological diseases.